2014
DOI: 10.2478/s11756-013-0328-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of indoleacetic acid, gibberellic acid and ethylene synthesized in vitro by Fusarium culmorum strains with different effects on cereal growth

Abstract: Three different Fusarium culmorum strains having a pathogenic, a deleterious (deleterious rhizosphere microorganism), or a promoting (plant growth promoting fungus) effect on plant growth were studied for their ability to synthesize in vitro the phytohormones indoleacetic acid (IAA), gibberellic acid (GA), and ethylene. All the phytohormones tested were synthesized in cultures supplemented with wide concentration ranges of glucose and tryptophan or methionine (precursors of phytohormone synthesis). The amounts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 73 publications
(73 reference statements)
0
28
0
Order By: Relevance
“…The IAA, the main auxin, is crucial for the majority of plant growth and development processes “and it is also a major factor determining the competition between fungal species that occupy the same niche [ 15 ]”. The production of microbial IAA may depend on the presence of its precursor, tryptophan; however, some microorganisms and plants can also synthesize IAA by Trp-independent mechanism [ 20 , 39 ]. According to Quiroz-Villareal et al [ 16 ], this amino acid was identified as one of the components of root exudates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The IAA, the main auxin, is crucial for the majority of plant growth and development processes “and it is also a major factor determining the competition between fungal species that occupy the same niche [ 15 ]”. The production of microbial IAA may depend on the presence of its precursor, tryptophan; however, some microorganisms and plants can also synthesize IAA by Trp-independent mechanism [ 20 , 39 ]. According to Quiroz-Villareal et al [ 16 ], this amino acid was identified as one of the components of root exudates.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the concentration of IAA in “MV DEM32” cultures was correlated with the initial dose of Trp at “9 °C” and 20 °C “( Figure 3 B,F), but in the presence of 1.5 mM of Trp, the MV DEM32 strain synthesized the highest amount of phytohormone (about 32 µg mL) ( Figure 3 D). Many reports confirmed that even the very small amount of Trp may induce the IAA synthesis, but in fact, the term ‘small dose’ is not clearly defined [ 15 , 17 , 20 , 39 ]. Kumar et al [ 18 ] announced the IAA concentrations in cultures of bacteria with the 4 mM dose of Trp, whereas Khan et al [ 39 ] applied 0.4 mM of IAA precursor.” The optimal dose of Trp recommended for fungal cultures is from 2 mM to 4 mM and the maximal concentration of IAA was usually measured after 60 and 72 h of incubation [ 17 , 40 ], “whereas the lowest threshold value indispensable for auxin synthesis is not defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of IAA reached 38850 ppm (unpublished data) in consequence of triplicate performed. In the other studies, it was observed that the production rates of various fungi were lower and their incubation periods were longer (Palavan-Unsal, 1993;Yalcinkaya, 1993;Khan et al, 2012;Jaroszuk-Ściseł et al, 2014). The increasing of the production level and the shortness of the incubation period are significant in terms of reducing the production cost.…”
Section: Resultsmentioning
confidence: 94%
“…Earlier studies of the three tested strains of Fusarium culmorum showed a clear diversity of their interaction with cereals, colonization of root [58,60] and root border cells [59] and the ability to synthesize toxins [58], CWDEs [63,64] and phytohormones [60,65]. The ability to induce plant resistance has been demonstrated for these Fusarium culmorum strains [58].…”
Section: Eps Antioxidant Propertiesmentioning
confidence: 97%